Epigenetic Therapy as a Putative Molecular Target to Modulate B Cell Biology and Behavior in the Context of Immunological Disorders. (8th February 2020) - da Costa, Thayse Pinheiro; El-Cheikh, Marcia Cury; Carneiro, Katia
Abstract : Histone Deacetylase- (HDAC-) dependent epigenetic mechanisms have been widely explored in the last decade in different types of malignancies in preclinical studies. This effort led to the discovery and development of a range of new HDAC inhibitors (iHDAC) with different chemical properties and selective abilities. In fact, hematological malignancies were the first ones to have new iHDACs approved for clinical use, such as Vorinostat and Romidepsin for cutaneous T cell lymphoma and panobinostat for multiple myeloma. Besides these promising already approved iHDACs, we highlight a range of studies focusing on the HDAC-dependent epigenetic control of B cell development, behavior, and/or function. Here, we highlight 21 iHDACs which have been studied in the literature in the context of B cell development and/or dysfunction mostly focused on B cell lymphomagenesis. Regardless, we have identified 55 clinical trials using 6 out of 21 iHDACs to approach their putative roles on B cell malignancies; none of them focuses on peritoneal B cell populations. Since cells belonging to this peculiar body compartment, named B1 cells, may contribute to the development of autoimmune pathologies, such as lupus, a better understanding of the HDAC-dependent epigenetic mechanisms that control its biology and behavior might shed light on iHDAC use to manage these immunological dysfunctions. In this sense, iHDACs might emerge as a promising new approach for translational studies in this field. In this review, we discuss a putative role of iHDACs in the modulation of peritoneal B cell subpopulation's balance as well as their role as therapeutic agents in the context of chronic diseases mediated by peritoneal B cells.